Population-level benefits of increasing influenza vaccination uptake among Italian older adults: results from a granular panel model - Domnich, Alexander; Orsi, Andrea; Panatto, Donatella; Ogliastro, Matilde; Barca, Alessandra; Bert, Fabrizio; Cereda, Danilo; Chironna, Maria; Costantino, Claudio; Fiacchini, Daniel; Pariani, Elena; Rizzo, Caterina; et al. (Frontiers in Public Health, 2023)
The impact of seasonal influenza vaccination (SIV) on mortality is still controversial; some studies have claimed that increasing vaccination coverage rates is beneficial, while others have found no significant association. This study aimed to construct a granular longitudinal dataset of 2 This is a provisional file, not the final typeset article local VCRs and assess their effect on pneumonia-and influenza-related (P&I) mortality among Italian adults aged ≥ 65 years.Methods: NUTS-3 (nomenclature of territorial units for statistics) level data on SIV coverage were collected via a survey of local data holders. Fixed-and random-effects panel regression modeling, when adjusted for potential confounders, was performed to assess the association between local SIV coverage rates and P&I mortality in older adults.Results: A total of 1,144 local VCRs from 2003 to 2019 were ascertained. In the fully adjusted fixed-effects model, each 1% increase in vaccination coverage was associated (P < 0.001) with a 0.6% (95% CI: 0.3-0.9%) average over-time decrease in P&I mortality. With an annual average of 9,293 P&I deaths in Italy, this model suggested that 56 deaths could have been avoided each year by increasing SIV coverage by 1%. The random-effects model produced similar results. The base-case results were robust in a sensitivity analysis.Over the last two decades, Italian jurisdictions with higher SIV uptake had, on average, fewer P&I deaths among older adults. Local policy-makers should implement effective strategies to increase SIV coverage in the Italian senior population.